2014
DOI: 10.1086/677570
|View full text |Cite
|
Sign up to set email alerts
|

Aging, Life Span, and Energetics under Adult Dietary Restriction in Lepidoptera

Abstract: Stressful conditions can affect resource allocation among different life-history traits. The effect of dietary restriction (DR) on longevity and reproduction has been studied in many species, but we know little about its effects on energetics, especially in flying animals that have high energy demand. We assessed the effects of DR on metabolic rate throughout the entire adult life span in two butterfly species, Colias eurytheme and Speyeria mormonia. We cut the food intake of adult females in half and measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 69 publications
3
30
3
Order By: Relevance
“…EL butterflies reduced their RMR under food stress, which would save energy that could be subsequently used for reproduction. Food stress reduced RMR in a few other flying insects [5,25]. Butterflies used in our experiments were wild-caught, young adults, which all had briefly experienced nectar conditions in the landscape of origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EL butterflies reduced their RMR under food stress, which would save energy that could be subsequently used for reproduction. Food stress reduced RMR in a few other flying insects [5,25]. Butterflies used in our experiments were wild-caught, young adults, which all had briefly experienced nectar conditions in the landscape of origin.…”
Section: Discussionmentioning
confidence: 99%
“…Income breeders rely on nectar consumption (or alternative feeding resources). Nectar intake positively affects life-history traits in several species [5,6]. Nectar is composed of water and sugars (mainly sucrose, fructose and glucose), and also amino acids [7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, chronic caloric restriction reduces fecundity in many animals while lifespan is prolonged [ 11 ]. In our study organism, the butterfly Speyeria mormonia (Nymphalidae), lifespan is not affected by adult food restriction but reproductive output depends on adult feeding [ 12 , 13 ]. Here we examine the effects of a pulling force on the network, through increased flight.…”
Section: Introductionmentioning
confidence: 99%
“…However, we also found that oxidative damage decreased with age. This suggests that older butterflies have reduced their production of ROS compared with younger ones, for instance by reducing metabolic rate as observed in other Lepidoptera (Niitepõld and Hanski 2013;Niitepõld et al 2014). Antioxidant defences were found to increase while oxidative damage tended to decrease with mating frequency.…”
Section: Discussionmentioning
confidence: 67%